Proses Penciptaan Bejana Keramik Bahan Paper Clay. The Process of Creating Ceramic Vessels Using Paper Clay - Perpustakaan UGM, i-lib ([Yogyakarta] : Program Studi Ilmu Keperawatan Fak. Kedokteran UGM, 2000)
Nowadays, ceramic arts as an artistic craft product has developed promisingly in Indonesia